Iowa RBA, May 24, 1999 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1999)
Email for the Iowa RBA for May 24, 1999. Highlights include Clark's Grebe, Western Grebe, Snowy Egret, and Mississippi Kite. Includes notes for updates for May 26. Epson - sheet feed/flatbed